ISOLASI NEMATODA PATOGEN SERANGGA STEINERNEMA DAN HETERORHABDITIS - Chaerani, Y. Suryadi, T.P. Priyatno, D. Koswanudin1, U. Rahmat , Sujatmo, Yusuf, dan C.T. Griffin. (Universitas Lampung, 2007)
Isolation of Entomopathogenic Nematodes Steinernema and Heterorhabditis. Entomopathogenic nematodes from the genus Steinernema and Heterorhabditis (Rhabditida: Steinernematidae and Heterorhabditidae) are promising biological control agent of insect pests. Indigenous nematodes have been isolated and collected for the use in local biological control program of important insect pests. The nematodes were isolated using soil baiting method with insect larvae. Laboratory tests have shown that the mealworm larvae Tenebrio molitor (Coleoptera: Tenebrionidae) served as a good alternative to the standard insect bait, the greater wax moth larvae Galleria mellonella (Lepidoptera: Galleriidae) for isolation and maintenance of nematodes. Both nematodes were successfully isolated using T. molitor larvae from 13% soil samples (26 out of a total of 207) collected from 14 locations in West and Central Java and Lampung provinces in the period of 1993 until 2006. Heterorhabditis (9%) was more prevalent than Steinernema (4%). Both nematodes were successfully propagated on mealworm larvae.